Impact of science and technology fiscal expenditure on green innovation: moderating role of environmental decentralization - Shiqian Hu; Yingzhen Lin; Wei Lu; Md. Kamal Uddin (International Journal of Climate Change Strategies and Management)
Purpose – Science and technology fiscal expenditure (STFE) is critical in advancing technological breakthroughs and fostering talent, thus driving green innovation forward. Moreover, Chinese-style environmental decentralization (ED) operates within the framework of “political centralization and economic decentralization,” varying degrees of ED come with different political and economic incentives, shaping the fiscal expenditure preferences of local governments. This study aims to explore the nonlinear effects of STFE on green innovation as influenced by different degrees of ED, thus supporting policymakers in formulating precise fiscal incentive policies to enhance the effect of STFE on green innovation. Design/methodology/approach – This study develops a partially linear functional-coefficient model to analyze how the degree of ED could shape the impact of STFE on green innovation using the panel data of 284 Chinese cities from 2007 to 2021. Findings – The findings reveal that, with the increasing degree of ED, the impact of STFE on green innovation exhibits an inverted U-shaped trend, which confirms that a moderate degree of ED is more conducive to harnessing the incentive effect of such expenditure. The effect of different degrees of ED on the relationship between STFE and green innovation varies with the heterogeneity of urban resource endowment. In addition, cities characterized by higher levels of ED can effectively enhance the quantity and quality of green innovation through STFE. Originality/value – First, the study innovatively uses a partially linear functional-coefficient model to explore the nonlinear effects of STFE on green innovation as influenced by different degrees of ED. Second, this study expands the empirical analysis of the moderating effects of ED on the relationship between STFE and green innovation, including robustness test and heterogeneity analysis.